Baicalin Exerts Anti-Airway Inflammation and Anti-Remodelling Effects in Severe Stage Rat Model of Chronic Obstructive Pulmonary Disease. (8th October 2018) - Wang, Genfa; Mohammadtursun, Nabijan; Lv, Yubao; Zhang, Hongying; Sun, Jing; Dong, Jingcheng
Abstract : Chronic obstructive pulmonary disease (COPD) is a worldwide epidemic. Current approaches are disappointing due to limited improvement of the disease development. The present study established 36-week side stream cigarette smoke induced rat model of COPD with advanced stage feature and evaluted the effects of baicalin on the model. Fifty-four Sprague–Dawley rats were randomly divided into six groups including room air control, cigarette smoke exposure, baicalin (40 mg/kg, 80 mg/kg, and 160 mg/kg), and budesonide used as a positive control. Rats were exposed to cigarette smoke from 3R4F research cigarettes. Pulmonary function was evaluated and pathological changes were also observed. Cytokine level related to airway inflammation and remodelling in blood serum, bronchoalveolar lavage fluid, and lung tissue was determined. Blood gases and HPA axis function were also examined, and antioxidant levels were quantified. Results showed that, after treatment with baicalin, lung function was improved and histopathological changes were ameliorated. Baicalin also regulated proinflammatory and anti-inflammatory balance and also airway remodelling and anti-airway remodelling factors in blood serum, bronchoalveolar lavage fluid, and lung tissue. Antioxidant capacity was also increased after treatment with baicalin in COPD rat model. HPA axis function was improved in baicalin treated groups as compared to model group. Therefore, baicalin exerts lung function protection, proinflammatory and anti-inflammatory cytokine regulation, anti-airway remodelling, and antioxidant role in long term CS induced COPD model.